Literature Review: The Influence of Truss Configuration and Height on Steel Truss Bridges Based on Deflection and Structural Weight - Sari, Wulan; Delitriana, Arvila; Gunadi, Riawan (Fakultas Teknik Universitas Tanjungpura, 2025)
In the design of steel truss bridges, selecting the appropriate truss configuration and height is a critical step that significantly impacts the overall structural performance. Steel truss bridges feature various configurations with distinct structural characteristics related to span length, structural weight, and deflection. Deflection serves as a key parameter to assess structural stiffness, while structural weight greatly influences the economic feasibility of the bridge design. Achieving weight efficiency without compromising structural performance can effectively reduce construction costs, resulting in a strong and economical bridge. Based on a review of multiple studies, it is evident that both truss configuration and height strongly affect deflection and total structural weight. Among Indonesia's four common truss types